Diseño e implementación de un software educativo para reforzar el proceso de enseñanza aprendizaje de la unidad de bioquímica en los estudiantes del tercer curso de bachillerato de la especialidad de químico – biológicas de la unidad educativa Vicente Anda Aguirre sección diurna “LA DOLOROSA”, periodo académico 2012 -2013 - Sarmiento Zumba, Jorge Rolando (2015)
The Superior Chemistry curriculum contents in the third year of high school are very broad, which has caused that it’s so difficult to develop them in the allowed time, leaving unfinished or without depth study an important curricular unit, especially for students who wish to study chemical engineering, medicine or related careers in universities, such as Biochemistry, making it necessary to have a didactic multimedia support about this this block in order to be the students generate their own knowledge. That is the reason why it has set as a thesis work the DESIGN AND IMPLEMENTATION OF AN EDUCATIONAL SOFTWARE TO ENHANCE THE TEACHING-LEARNING PROCESS OF THE BIOCHEMISTRY UNIT WITH THE STUDENTS OF THIRD YEAR OF HIGH SCHOOL SPECIALTY CHEMICAL - BIOLOGICAL OF THE UNIDAD EDUCATIVA VICENTE ANDA AGUIRRE SECCIÓN DIURNA “LA DOLOROSA”, ACADEMIC YEAR 2012 -2013. To make possible the research work a general objective was raised: Design and implement an educational software to enhance the Teaching Learning Process of the Biochemistry Unit with the Third Year of High School students of the Chemical - Biological Specialty of the Unidad Educativa Vicente Anda Aguirre Sección Diurna “La Dolorosa”, which was achieved through different activities such as collecting information on the contents of the biochemistry unit to synthesize them in the educational software, in addition to implementing a development methodology software that fits the activities, content and multimedia exercises, then the educational software was designed taking into account the main elements of the contents of the biochemistry unit to generate significant learning knowledge; finally, the final work was validated and socialized with teachers and students of the Third Year of High School Specialty Chemical and Biological Sciences. During the entire creation process it has been the assistance of the chemistry teacher and Vice Principal of the Unidad Educativa Fiscomisional Vicente Anda Aguirre de la sección diurna “La Dolorosa”, with his help the Biochemistry unit outstanding issues were determined, self-assessments were developed, videos were searched, all with the purpose of creating an educational software that can be used by students and teachers as an instructional support to study biochemistry. Once completed the educational multimedia it was socialized with the Chemistry teacher and students of the aforesaid high school, the same who had the acceptance of all because it is easy to use, and encourages learning through different graphs, videos and evaluations, making it a potential didactic tool for students and teachers in the unit of Biochemistry.